ANÁLlSE DAS CONDIÇÕES DE DESENVOLVIMENTO FAMILIAR EM NITERÓI: uso do IDF e GINI. - José Nilton de Sousa (Universidade Federal do Maranhão, 2010)
The present study applies the I.D.F with the Gini Indexes in the Carioca city of Niterói and its ponderation zones. Niteroi occupies the 3° position at the hanking of IDH in the country and jumps to the first place considering the Rio de Janeiro State . The conditions of the families studied are following the developing of the AREAP, presenting a social- spatial hierarchy. The IDF refaring the access to knowledge and to work present results one should worry about. In the other hand the biggest IDF considered areas correspond to the smallest Gini Index achieved and vice versa, proving the relation of the income distribution of those families are related to the AREAT.